Detachment‐Based Equilibrium of Anoikic Cell Death and Autophagic Cell Survival Through Adaptor Protein p66Shc. Issue 3 (25th December 2015) - Cai, Zeyuan; Zhao, Dan; Sun, Yanan; Gao, Dan; Li, Xia; Yang, Jie; Ma, Zhenyi
ABSTRACT: Anoikis (detachment‐induced cell death) confers a tumor‐suppressive function in metastatic cancer cells. Autophagy, a conserved self‐degradative process, enhances the anoikis resistance of detached cancer cells by maintaining cellular homeostasis. However, the mechanism of regulating cell fate‐decision by balancing anoikis and autophagy has been poorly understood. Our previous studies have shown that the adaptor protein p66 Shc mediates anoikis through RhoA activation and inhibits tumor metastasis in vivo . We also found that p66 Shc depletion mitigates nutrient‐deprivation‐induced autophagy. These findings suggest p66 Shc may coordinately regulate these two processes. To verify this hypothesis, we investigated the effect of p66 Shc on the cell death of detached lung cancer cells, and measured autophagy markers and autophagic flux. Results showed that p66 Shc depletion significantly inhibited anoikis, and reduced the formation of LC3B‐II and the degradation of Sequestosome 1 (SQSTM1, p62) in detachment‐induced cells. Using monodansylcadaverine (MDC)‐LysoTracker double staining and monomeric Cherry (mCherry)‐GFP‐LC3 assay, we found that the autophagic flux was also mitigated by p66 Shc depletion. In addition, p66 Shc knockdown increased the formation of full‐length X‐linked inhibitor of apoptosis (XIAP)‐associated factor 1 (XAF1), which enhances anoikis sensitivity. In conclusion, p66 Shc plays an essential role in detachment‐based equilibrium of anoikic cell death and autophagic cell survival. Anat Rec, 299:325–333, 2016. © 2015 Wiley Periodicals, Inc.